The circadian cryptochrome, CRY1, is a pro-tumorigenic factor that rhythmically modulates DNA repair - Ayesha A. Shafi (Nature Portfolio, 2021)
Cryptochrome 1 (CRY1) is a transcriptional coregulator associated with the circadian clock. Here the authors reveal that CRY1 is hormone-regulated, stabilized by genomic insult, and promotes DNA repair and cell survival through temporal transcriptional regulation.